Synthesis and pharmacological evaluation of novel 1,3,8- and 1,3,7,8-substituted xanthines as adenosine receptor antagonists - José Enrique Rodríguez-Borges (2010)
A number of novel xanthines bearing a variety of substituents at positions 1, 3, 7 and 8 were prepared and evaluated for their binding affinity to the human adenosine receptor A1, A2A, A2B and A3 subtypes. Several of the 1,3,8- and 1,3,7,8-substituted xanthines showed moderate-to-high affinity at human A2B and A1 receptors, with the most active compound (14q) having a pKi of 7.57 nM for hA2B receptors and a selectivity over hA2A receptors of 8.1-fold and hA1 receptors of 3.7-fold.